Long hidden sepsis subgroup may benefit from immune therapy - Tidswell, Mark (Journal of Emergency and Critical Care Medicine; Vol 2 (December 2018): Journal of Emergency and Critical Care Medicine, 2018)
Sepsis syndrome includes an immediate inflammatory, or innate immune, response to infection that may be followed by mild or severe organ failure, excessive or depressed inflammation, survival, or death in more than 25% of patients. Research in animal models indicates that excessive inflammation increases early mortality, and targeted anti-inflammatory therapies reliably decrease mortality (1). Unfortunately, targeting inflammatory pathways in human clinical trials has not reduced patient mortality. Possible explanations for lack of response in humans include the heterogeneity of the sepsis syndrome in terms of cause and patient responses: micro-organism, site of infection, chronic patient illness, genomic program of inflammation, or timing of therapy in relation to onset of infection (2). An important element for future clinical trials will be to better characterize patients and match with one or more therapies most likely to reduce mortality.